Social-Psychological Profiles of Early Adolescents Involved in Bullying Activities - Georgiou, Stelios N; Stavrinides, Panayiotis (International Journal of Criminology and Sociology, 2012)
The purpose of the present study was to examine the differences existing between sub-groups of early adolescents involved in bullying activities at school. Specifically, the study aimed at comparing three identified groups (bullies, passive victims and aggressive victims or bully-victims) as well as uninvolved students in terms of a number of indicators of psycho-social adjustment; namely, empathy, impulsivity, hyperactivity, emotional and behavioral problems and pro-social skills. A representative sample of 454 Greek Cypriot students (mean age of 13.4) was selected from seven different public high schools. The participants completed a revised version of the Bullying and Victimization Questionnaire and based on their scores they were classified into one of four, mutually exclusive categories, those of bullies, victims, aggressive victims, and uninvolved. These groups were then compared regarding their mean scores on the Basic Empathy Scale, the Strengths and Difficulties Questionnaire, and the Urgency Subscale. Multiple post-hoc comparisons revealed that the aggressive victims group had the most problematic psycho-social profile. Specifically, aggressive victims were significantly more impulsive, less affectively empathic, and had lower prosocial skills, more behavioural problems and more hyperactivity. The results of the present study show that children and adolescents diagnosed as aggressive victims are at higher risk in a number of psychopathological characteristics that endanger typical development.